Phytochemical Characterization of Dillenia indica L. Bark by Paper Spray Ionization-Mass Spectrometry and Evaluation of Its Antioxidant Potential Against t-BHP-Induced Oxidative Stress in RAW 264.7 Cells - Md Badrul Alam; Arif Ahmed; Syful Islam; Hee-Jeong Choi; Md Abdul Motin; Sunghwan Kim; Sang-Han Lee (MDPI AG, 2020)
The antioxidant effects of the ethyl acetate fraction of Dillenia indica bark (DIBEt) and the underlying mechanisms were investigated in tert-butyl hydroperoxide (t-BHP)-stimulated oxidative stress in RAW 264.7 cells. Paper spray ionization-mass spectroscopy with positive-ion mode tentatively revealed 27 secondary metabolites in D. indica bark extract; predominant among them were alkaloids, phenolic acids, and flavonoids. A new triterpenoid (nutriacholic acid) was confirmed in DIBEt for the first time. DIBEt had strong free radical-scavenging capabilities and was also able to reduce t-BHP-induced cellular reactive oxygen species (ROS) generation in RAW 264.7 cells. DIBEt was found to prevent oxidative stress by boosting the levels of heme oxygenase-1 (HO-1) through the up-regulation of nuclear factor erythroid 2-related factor 2 (Nrf2) via the regulation of extracellular signal-regulated kinase (ERK) phosphorylation in RAW 264.7 cells. These results support the potential of DIBEt for defense against oxidative stress-stimulated diseases.